2009
DOI: 10.5650/jos.58.195
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior and Froth Stability in a Water/Lysophospholipid System

Abstract: Phase behavior in a water/lysophospholipid system was investigated. A hydrated solid phase is observed at low temperature. Above the melting temperature of the hydrated solid a micellar phase at low surfactant concentration and a liquid crystalline phase at high surfactant concentration were observed. Similarly to poly(oxyethylene)-type nonionic surfactant systems, clouding behavior takes place at high temprature. The concentration of micelle-liquid crystal transition shifts to higher surfactant concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A micellar phase appears at low LPL concentrations below 10 and a lamellar liquid crystalline phase appears at high concentrations. Below the Krafft point, a β-type hydrated solid is formed 21 but it changes to an α-type solid upon mixing with long-chain alcohols 22 . It has been shown that the effects of pH and of polyols and electrolytes, which are often added to cosmetics, on the phase behaviors of LPL/water systems are small 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A micellar phase appears at low LPL concentrations below 10 and a lamellar liquid crystalline phase appears at high concentrations. Below the Krafft point, a β-type hydrated solid is formed 21 but it changes to an α-type solid upon mixing with long-chain alcohols 22 . It has been shown that the effects of pH and of polyols and electrolytes, which are often added to cosmetics, on the phase behaviors of LPL/water systems are small 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Below the Krafft point, a β-type hydrated solid is formed 21 but it changes to an α-type solid upon mixing with long-chain alcohols 22 . It has been shown that the effects of pH and of polyols and electrolytes, which are often added to cosmetics, on the phase behaviors of LPL/water systems are small 21 . It has also been reported that when an LPL was used as an emulsifier, the emulsions stability against electrolyte addition or pH change was improved 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized that lysophospholipid LPL , which is obtained by the hydrolysis of a phospholipid, can solubilize a larger amount of Chol in the molecular assembly than phospholipid, due to the shape of the molecule 25 . Therefore, we investigated the formation of an L o phase as a potential cosmetic base material in cosmetics by mixing Chol with lysophospholipid, which can dissolve a large amount of Chol and which exhibits a high moisturizing effect 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that lysophopholipids have higher HLB value, lower surface tension and interfacial tension than phospholipids depending on the degree of hydrolysis, and these parameters become constant values when the degree of hydrolysis exceeds 80 11,12 . Krafft point and cloud point are present in the phase behavior of LPL/water system, where micellar phase appears at low concentration range less than 10 , lamellar liquid crystal phase appears at high concentration range above 10 , and lysophospholipid is found as β-type hydrated solid below Krafft point 13 . Moreover, it has also been verifi ed that effect of pH, polyol and electrolyte, which are often mixed with cosmetics, is small on the phase behavior in the LPL/ water system 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Krafft point and cloud point are present in the phase behavior of LPL/water system, where micellar phase appears at low concentration range less than 10 , lamellar liquid crystal phase appears at high concentration range above 10 , and lysophospholipid is found as β-type hydrated solid below Krafft point 13 . Moreover, it has also been verifi ed that effect of pH, polyol and electrolyte, which are often mixed with cosmetics, is small on the phase behavior in the LPL/ water system 13 . In addition, it was reported that when lysophospholipid was used as emulsifier, emulsion stability against electrolyte or pH increased 14,15 .…”
Section: Introductionmentioning
confidence: 99%